Narratives of Systemic Barriers and Accessibility: Poverty, Equity, Diversity, Inclusion, and the Call for a Post-Pandemic New Normal - Ciuffetelli Parker, Darlene; Conversano, Palmina (Frontiers in Education, 2021)
This paper captures the intimate, intensely lived, and storied experiences during the pandemic, on teachers’ narratives of teaching and education. The narratives illuminate deep knowledge and insight into pre-existing school systemic barriers prior to the pandemic, and how those same barriers are magnified during the pandemic in what has become a global watershed moment that calls for equity reform in school systems. A narrative theoretical framework is used, as well as an ethic of care framework that informs the study. Issues of income equity, diversity, and inclusion are illuminated, with further focus on topics of technology access, streaming, resilience, and teacher-student identity and relationship. Recommendations to eradicate systemic barriers in schools are explored, highlighting suggestions for equity reform in areas that include: enhancing professional practice; building a school culture of care, and; developing partnerships and relationships.